Trafficking in Persons for Organ Transplantation: A Legal Analysis of Criminal Liability and Enforcement Challenges - Enik Isnaini; Muhammad Syakir al-kautsar; Fajar Seto Nugroho; Adelia Bilqis Muhklisati Suaidah (Universitas Islam Lamongan, 2026)
This study discusses the crime of human trafficking committed with the purpose of taking and transplanting victims' organs. This criminal act is a modern form of human exploitation that involves illegal networks between countries, taking advantage of economic inequality and the scarcity of legal organs. The research method used is normative (literature), with a statutory approach and a conceptual approach. Legal sources include international legal instruments such as the Palermo Protocol, the United Nations Convention against Transnational Organized Crime, as well as national regulations such as Law No. 21 of 2007 concerning the Eradication of the Crime of Trafficking in Persons and Law No. 36 of 2009 concerning Health (especially related to organ transplantation). The results of the study show that although normative laws and regulations have prohibited the practice of trafficking in persons for organ transplantation, there are still weaknesses in the coordination of law enforcement between agencies, difficulties in proving elements of exploitation, and regulatory gaps related to organ transplantation between countries that are not strictly supervised. The conclusion of this study emphasizes the need for harmonization between criminal law and health law, increasing international cooperation, and strengthening the organ transplant supervision system to effectively prevent and crack down on human trafficking for organ transplantation